“That Came Back to Haunt Me”: Violence Against Women Survivors’ Concerns About Police Use of Body-Worn Cameras - Couture-Carron, Amanda (Journal of interpersonal violence, 2026)
Despite the substantial contact police have with survivors of violence against women, empirical accounts of survivors’ perceptions of police use of body-worn cameras (BWCs) are limited. This study examines survivors’ concerns with BWCs. We present qualitative data from semi-structured interviews with 33 survivors of intimate partner abuse and sexual assault. While the majority (79%, n = 26) of the women in this study support police use of BWCs, most (90%, n = 30) still express concerns with the technology. Survivors’ concerns fell into three main areas: fear of BWCs capturing trauma responses that could be used against survivors, BWCs decreasing survivor comfort and reporting, and BWCs revictimizing survivors and contributing to survivors’ loss of control. The findings reveal concerns that police can work to address to avoid survivor–police relations being deteriorated by police use of BWCs.